Effective exchange rates, current accounts and global imbalances - Joscha Beckmann; Robert Czudaj (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2016)
This study analyzes the dynamics between real effective exchange rates and current accounts from a novel perspective. We start by dissecting long-run and time-varying short-run dynamics as well as causalities between both variables. Following this, we extend our framework by including short-term interest rates. Finally, we examine common exchange rate and current account dynamics across countries based on common factors. Our results show that a real appreciation coincides with a worsening of the current account in most cases. The adjustment pattern is time-varying but suggests that the causality mainly runs from effective exchange rates to current accounts. However, an extension of our framework based on monthly data shows that trade balance adjustment is observed less frequently, suggesting that valuation effects play an important role for the relationship between current accounts and exchange rates. From a global point of view, cross-country trends which drive exchange rates and current accounts also share similar dynamics over the long-run, which is an important finding in the context of global imbalances. – – Diese Studie analysiert die Dynamik zwischen realen effektiven Wechselkursen und Leistungsbilanzen aus einem neuen Blickwinkel. Um Kausalitäten zwischen den beiden Variablen adäquat zu untersuchen, wird mit der Zerlegung der langfristigen und zeitlich variierenden kurzfristigen Dynamiken begonnen. Anschließend wird der Ansatz um kurzfristige Zinsen erweitert, um geldpolitische Schocks in die Analyse mit einzubeziehen. Abschließend werden Wechselkurs- und Leistungsbilanzdynamiken in Form von gemeinsamen Faktoren über Länder hinweg untersucht. Die Ergebnisse zeigen, dass in den meisten Fällen eine reale Aufwertung mit einer Verschlechterung der Leistungsbilanz einhergeht. Das Anpassungsmuster verändert sich jedoch über die Zeit und deutet darauf hin, dass die Kausalität in erster Linie von effektiven Wechselkursen in Richtung Leistungsbilanz läuft. Eine Erweiterung des Ansatzes basierend auf monatlichen Daten zeigt, dass eine Reaktion der Handelsbilanz auf Wechselkursänderungen weniger häufig zu beobachten ist. Dies deutet darauf hin, dass Bewertungseffekte für Interdependenzen zwischen Leistungsbilanzen und Wechselkursen eine wichtige Rolle spielen.
Keywords: F31; F32; 330; current account; global imbalances; Markov-switching; multivariate cointegration; real exchange rates